2016
DOI: 10.5530/ijopp.9.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cardiovascular Diseases in a Tertiary Care Teaching Hospital

Abstract: Background: Cardiovascular disease (CVD) comprises the most prevalent serious disorders in the developed and developing nations. Epidemiological studies have played an important part in the elucidation of predisposing factors for CVD and opportunities for prevention and treatment. The present study is designed retrospectively to focus on prevalence of various CVD and causes of mortality in patients admitted to cardiology unit. Materials and Methods: A retrospective epidemiological study was conducted in the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Interestingly, we found that most patients were admitted with more than one CVD (Table 2), with uncontrolled hypertension being the most frequently encountered CVD in this study. The stratification of hypertension according to types of CVDs showed that it constitutes the common risk factor for almost all types of CVDs involved in this study (Table 5), in agreement with numerous hospital-based studies worldwide [12][13][14][15][16][17]. Delay in treating hypertension leads to complications and, consequent, high mortality.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, we found that most patients were admitted with more than one CVD (Table 2), with uncontrolled hypertension being the most frequently encountered CVD in this study. The stratification of hypertension according to types of CVDs showed that it constitutes the common risk factor for almost all types of CVDs involved in this study (Table 5), in agreement with numerous hospital-based studies worldwide [12][13][14][15][16][17]. Delay in treating hypertension leads to complications and, consequent, high mortality.…”
Section: Discussionsupporting
confidence: 87%
“…Epidemiological studies have played an important part in the elucidation of predisposing factors for COPD, CKD, acute pancreatitis and CLD and opportunities for prevention and treatment 2 . The present study is designed retrospectively to focus on prevalence of various COPD, CKD, acute pancreatitis and CLD and causes of mortality in patients admitted to respective speciality units 3 .…”
mentioning
confidence: 99%